Predictors of Mortality Among Hospitalized Patients With Lower Respiratory Tract Infections in a High HIV Burden Setting. (15th December 2018) - Worodria, William; Chang, Emily; Andama, Alfred; Sanyu, Ingvar; Byanyima, Patrick; Musisi, Emmanuel; Kaswabuli, Sylvia; Zawedde, Josephine; Ayakaka, Irene; Sessolo, Abdul; Lalitha, Rejani; Davis, John Lucian; et al.
Abstract : Introduction: Lower respiratory tract infections (LRTIs) are a leading cause of mortality in sub-Saharan Africa. Triaging identifies patients at high risk of death, but laboratory tests proposed for use in severity-of-illness scores are not readily available, limiting their clinical use. Our objective was to determine whether baseline characteristics in hospitalized participants with LRTI predicted increased risk of death. Methods: This was a secondary analysis from the Mulago Inpatient Non-invasive Diagnosis-International HIV-associated Opportunistic Pneumonias (MIND-IHOP) cohort of adults hospitalized with LRTI who underwent standardized investigations and treatment. The primary outcome was all-cause mortality at 2 months. Predictors of mortality were determined using multiple logistic regression. Results: Of 1887 hospitalized participants with LRTI, 372 (19.7%) died. The median participant age was 34.3 years (interquartile range, 28.0–43.3 years), 978 (51.8%) were men, and 1192 (63.2%) were HIV-positive with median CD4 counts of 81 cells/µL (interquartile range, 21–226 cells/µL). Seven hundred eleven (37.7%) participants had a microbiologically confirmed diagnosis. Temperature <35.5°C [adjusted odds ratio (aOR) = 1.77, 95% confidence intervals (CI): 1.20 to 2.60; P = 0.004], heart rate >120/min (aOR = 1.82, 95% CI: 1.37 to 2.43; P < 0.0001), oxygen saturation <90% (aOR = 2.74, 95% CI: 1.97 to 3.81; P < 0.0001), being bed-bound (aOR = 1.88, 95% CI: 1.47 to 2.41; P < 0.0001), and being HIV-positive (aOR = 1.49, 95% CI: 1.14 to 1.94; P = 0.003) were independently associated with mortality at 2 months. Conclusions: Having temperature <35.5°C, heart rate >120/min, hypoxia, being HIV-positive, and bed-bound independently predicts mortality in participants hospitalized with LRTI. These readily available characteristics could be used to triage patients with LRTI in low-income settings. Providing adequate oxygen, adequate intravenous fluids, and early antiretroviral therapy (in people living with HIV/AIDS) may be life-saving in hospitalized patients with LRTI. Abstract : Supplemental Digital Content is Available in the Text.